Analysis of Regional Market Management: JEL Classification: H7, L3, R5, Q5, O21 - Mawahda, Nurul (Journal La Bisecoman, 2025)
This research aims to find out an overview of how the process of establishing markets in Sinjai Regency and how the application of regional market standardization in Sinjai Regency The research method used is descriptive research method, namely data collection techniques carried out by in dept interviews (in-depth interviews), observation, online data searches, and literature studies. The data obtained was then analyzed qualitatively by explaining and describing the data studied. The results of this study show that: (1) The management of regional markets in Sinjai Regency is regulated in Regional Regulation Number 10 of 2016 where in this Regional Regulation everything related to market management has been regulated; (2) The Sinjai Regency Government in this case involved in market management includes the Industry Trade and Energy Mineral Resources Office, as a regional device authorized by government affairs in the field of trade and UPTD as the person in charge of managing the market; (3) The process of establishing a market in this case is required to analyze the socio-economic conditions of the community and micro, small and medium enterprises in the vicinity; (4) The standardization carried out or contained in the Sinjai Regency Regional Regulation is a general Regional Regulation.